Investigation into pore structure regulation and CO2 adsorption mechanisms during PVC synergistic activation of gasification fine slag - Yue Lu; Ying Zhou; Xudong Song; Peng Lv; Jie Xu; Lei Li; Linmin Zhang; Yuchen Shi; Yonghui Bai; Guangsuo Yu; Min Yao (Fuel, 2027)

Hydroxyl-Mediated radical initiation and functional group activation for enhancing the oxidation activity of coal gasification fine Slag: Experimental and DFT study - Qingyun Wang; Xueqin Hai; Yonghui Bai; Peng Lv; Jiaofei Wang; Weiguang Su; Xudong Song; Guanghua Lu; Guangsuo Yu (Fuel, 2026)

Performance and mechanism investigation of CO2 adsorption materials prepared from rich carbon gasification fine slag and PVC synergy - Ying Zhou; Yue Lu; Mingxuan Yin; Xudong Song; Peng Lv; Qinghua Guo; Lei Li; Linmin Zhang; Yonghui Bai; Guangsuo Yu; Min Yao (Fuel, 2026)

Study on particle fragmentation characteristics during rapid pyrolysis of coal based on the structural characteristics of coal macerals - Guoping Ma; Peng Lv; Xudong Song; Yonghui Bai; Jiaofei Wang; Weiguang Su; Guangsuo Yu (Fuel, 2026)

Mechanisms of moisture-induced deformation in deep loess under constant head conditions - HUANG Xin; ZHENG Jianguo; YU Yongtang; ZHANG Weiwei; WANG Yuguo; HE Hong; WEN Yonghui (Transportation Geotechnics, 2026)

Fusicoccane glycosides from the endophytic fungus Talaromyces sp. DC-26 - Peng Zhou; Jingwen Yu; Xueying Deng; Jinyan Cai; Wenya Feng; Junjun Liu; Qin Li; Chong Dai; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

Mechanism of synergistic hydrogen production from agricultural and plastics waste co-gasification: A ReaxFF molecular dynamics study - Qifu Luo; Xueqin Hai; Yonghui Bai; Linmin Zhang; Weiguang Su; Jiaofei Wang; Xudong Song; Peng Lv; Guangsuo Yu (Waste Management, 2026)

Investigation of particle size effects and interfacial interaction mechanisms during froth flotation of coal gasification fine slag - Bin Liu; Peng Lv; Dongbin Mai; Yonghui Bai; Jiaofei Wang; Weiguang Su; Xudong Song; Guangsuo Yu (Fuel, 2026)

Analysis and identification of geographical indication protected Huangjiu based on multimodal data combined with chemometric methods - Xiaodan Liu; Qiuwen Shan; Xianhao Ding; Chao Ji; Yonghui Yu; Huang Dai; Fuwei Pi; Jiahua Wang; Ming Zhang (Food Control, 2026)

Nanoparticle transport in porous and fractured media: Size-exclusion-driven early arrival and aperture-dependent behavior - Yaqian Ren; Yanlong Kong; Changqian Cao; Yonghui Huang; Weizun Zhang; Jiacheng Yu; Jiyang Wang (Advances in Water Resources, 2026)

1H NMR-guided isolation of ophiobolins from Bipolaris maydis and their bioactivities - Yong Shen; Xiaotian Zhang; Qin Li; Mengru Yu; Yongqi Li; Luosheng Wan; Xing Sun; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

Facile green transformation of alkali lignin via laccase-mediated functionalization for high-performance lignin-based films - Jieyu Yang; Yingjie Wang; Yu Qin; Mizi Fan; Guanben Du; Yan Xia; Xiaojian Zhou; Yonghui Zhou; Jingjing Liao (Journal of Environmental Chemical Engineering, 2026)

Multi-objective optimization for integrated energy systems using non-dominated sorting genetic and swarm intelligence methods - Feng Li; Yonghui Chen; Ying Hu; Yang Yu; Lining Xing (Swarm and Evolutionary Computation, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Evaluation approach based on Timoshenko beam model for longitudinal response of shield tunnel to lateral excavation - Hao Li; Maosong Huang; Jian Yu; Yonghui Li; Yuancheng Guo (Tunnelling and Underground Space Technology, 2026)

Overexpression of SlPMEI3 in tomato increased the viscosity of ketchup and juice - Chunyu Liu; Yonghui Zhu; John B. Golding; Penta Pristijono; Yue Guan; Youjian Yu; Yong He; Yongxin Li; Zhujun Zhu; Lei Ru (Plant Science, 2026)

Molecular model construction of pyrolyzed chars from Meihuajing coal Macerals and ReaxFF simulations into char gasification reaction mechanisms - Mingxuan Yin; Qifu Luo; Hua Ma; Yonghui Bai; Xudong Song; Jiaofei Wang; Weiguang Su; Peng Lv; Guangsuo Yu (Fuel, 2026)

Impact and mechanism of low-molecular-weight compounds in coal on soot formation during combustion - Xuanxuan He; Peng Lv; Xudong Song; Yonghui Bai; Jiaofei Wang; Weiguang Su; Guangsuo Yu (Fuel, 2026)

Effect mechanism of residual carbon on crystallization behavior of high-iron coal slag - Wei Zhao; Linmin Zhang; Wei Li; Xudong Song; Yuchen Li; Jiaofei Wang; Guoqiang Li; Yonghui Bai; Xia Liu; Guangsuo Yu (Fuel, 2026)

Export-attributed carbon footprint of cotton production in arid China: A life cycle and driver analysis - Jian Liu; Yu Zhang; Cun Chang; Shuai Wu; Wei Yan; Yonglong Han; Yonghui Wang; Xiaofei Ma (Agricultural Systems, 2026)

Spectral investigation of ignition and alkali metal release from single coal particles: Influence of particle size - Ying Zhou; Runmin Wu; Jinyun Li; Xudong Song; Peng Lv; Jiaofei Wang; Weiguang Su; Yonghui Bai; Guangsuo Yu; Min Yao (Fuel, 2026)

Mechanism of residue carbon formation in entrained-flow gasification fine slag: From the perspective of coal macerals - Hua Ma; Mingxuan Yin; Xiaqing Liu; Bin Liu; Yonghui Bai; Xudong Song; Peng Lv; Jiaofei Wang; Guanghua Lu; Guangsuo Yu (Fuel, 2026)

In-situ preparation of silicon carbide by Joule-heated carbothermal reduction: A new approach to high-value utilization of coal gasification fine slag - Yue Lu; Ziyue Wu; Ying Zhou; Xudong Song; Peng Lv; Jiaofei Wang; Weiguang Su; Yonghui Bai; Guangsuo Yu (Fuel, 2026)

Dynamic atomic-level study of slag structure and fluidity changes induced by the amphoteric transition of Al2O3 - Linmin Zhang; Wei Zhao; Chunlei Gao; Xudong Song; Yuchen Li; Juntao Wei; Weiguang Su; Yonghui Bai; Michael Müller; Guangsuo Yu (Fuel, 2026)

Occurrence characteristics and ecological risks of fluorescent whitening agents in water bodies around a landfill - Xuejing Yang; Mengfei Su; Yifei Wang; Yu Guo; Bo Yao; Shuwen Yan; Yonghui Han; Jiansheng Cui (Journal of Hazardous Materials, 2026)

Biodiversity gains importance in sustaining ecosystem multifunctionality when beyond aridity thresholds in temperate grasslands - Yu Yang; Changchao Zhang; Mingxing Tian; Binwei Ci; Cong Liu; Yunxiang Cheng; Pujin Zhang; Hongtao Luo; Liqing Zhao; Yonghui Wang; Wenhong Ma (Agriculture, Ecosystems & Environment, 2026)

First report of fruit rot caused by Fusarium avenaceum and Fusarium graminearum on Plum in Yunnan, China - Fenghuan Yang; Yonghui Cheng; Chao Yu; Yijuan Yang; Zhenghui Huang; Huamin Chen (Crop Protection, 2025)

Hydrodynamic characteristics of horizontal-axis tidal turbine with Gurney Flap and vortex generators - Yonghui Liu; Yuqi Liu; Yu Xue; Junzhe Tan; Peng Yuan; Xiancai Si; Zhen Pei; Rui Shu; Xiaodong Liu (Ocean Engineering, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Novel insights into sources identification of fluvial dissolved organic matter in intricate plain river networks using optical indices with grey influence analysis and Bayesian model - Dongping Liu; Feng Yang; Feng Qian; Yonghui Song; Huibin Yu (Analytica Chimica Acta, 2025)

Design and flow performance analysis of sediment core drilling tools for seafloor drill - Jialiang Wang; Youjia Hu; Siqi Hu; Mengfei Yu; Buyan Wan; Yonghui Tang (Marine Georesources & Geotechnology, 2025)

Novel developing an aqueous status fingerprint to identify tempo-spatial-multivariate elements of water quality in the seven major rivers into Northwestern Pacific - Dongping Liu; Benxin Yu; Hongjie Gao; Yonghui Song; Zhipeng Yao (Process Safety and Environmental Protection, 2025)

Study on high efficiency selective flocculation flotation of coal gasification fine slag with anionic polyacrylamide - Bin Liu; Peng Lv; Jinxin Li; Yonghui Bai; Jiaofei Wang; Weiguang Su; Xudong Song; Guangsuo Yu (Journal of Environmental Chemical Engineering, 2025)

Vegetation growth carryover and lagged climatic effect at Juniperus seravschanica different scales: From tree rings to remote sensing data - Jiuqi Chen; Yonghui Wang; Tongwen Zhang; Kexiang Liu; Shulong Yu; Kailong Guo; Zhihao He; Beihua Liang (Dendrochronologia, 2025)

Dissimilatory nitrate reduction to ammonium pathway during composting: Insight into key factors, functional microbes, and multi-factor interactions - Shuai Shi; Jiaxin Bao; Donghui Lv; Yonghui Xu; Zhiheng Guo; Jingjie Zhang; Shuai Ren; Yue Han; Ruixin Bi; Nana Jiang; Ning Wang; Jie Pan; et al. (Chemical Engineering Journal, 2025)

Recycling of spend graphite anodes in Fenton-like catalysis for green economy and long-term sustainable wastewater purification - Yu Peng; Qiming Zhang; Yonghui Fan; Ruixuan Su; Wei Ren; Xiao Xiao; Xubiao Luo (Chemical Engineering Journal, 2025)

A carbon-centered framework for ecosystem service supply-demand analysis in arid China: Insights for ecological zoning under dual carbon goals - Yonglong Han; Igboeli Emeka Edwin; Yonghui Wang; Wei Yan; Chun Luo; Wei Yu; Xiaofei Ma (Journal of Cleaner Production, 2025)

Interaction between phosphorus and alkali/alkaline earth metals and their effect on ash transformation thermal kinetics during phosphorus-rich biomass and coal co-gasification - Chaoyue Zhao; Yonghui Bai; Wei Zhao; Yuchen Li; Xudong Song; Jiaofei Wang; Weiguang Su; Peng Lv; Guangsuo Yu; Min Yao (Fuel, 2025)

Changes in soil organic carbon and its forms in recovering alpine meadows of various lengths in relation to altitude - Chunying Lin; Xilai Li; Huafang Sun; Xiaoxue Su; Hongmei Li; Rongna Liu; Chengyi Li; Yonghui Hou; Shizhen Zhu; Di Yu; Liyan Zhang; Jiexia Li; et al. (CATENA, 2025)

Rapid enrichment of anaerobic ammonia oxidation bacteria by combining low nitrogen strength with microbial viability - Heng Yu; Yue dong; Bing Li; Sike Wang; Junkai Zhao; Jiane Zuo; Yonghui Song; Chengtun Qu (Bioresource Technology, 2025)

Tailoring of a specific pH-induced self-enhanced photothermal cellulose hydrogel for antibiotic-resistant bacteria-infected wound treatment - Rimei Chen; Yonghui He; Lingli Tian; Yu Meng; Zhiping Chen; Nianfang Ma; Chunfang Wang; Hui He (Chemical Engineering Journal, 2025)

Decreased LTBP2 expression inhibits proliferation and migration of glioma - Yonghui Zhang; Yue Qin; Xiaochen Yu (Molecular & Cellular Toxicology, 2025)

Identification of nodule-inception-like protein (NLP) transcription factor family and analysis of their expression under abiotic stresses in Rhododendron henanense subsp. lingbaoense - Xiangli Yu; Yonghui Li; Wenwen Fan; Junwang Han; Yafang Zhang; Hailiang Wang; Xiaojun Zhou (Plant Biotechnology Reports, 2025)

Characteristics of CO2 gasification reaction and biochar structure evolution of rice straw in K2CO3-Na2CO3-Li2CO3 ternary molten salt - Hui She; Peng Lv; Xuanxuan He; Yonghui Bai; Jiaofei Wang; Xudong Song; Weiguang Su; Juntao Wei; Guangsuo Yu (Process Safety and Environmental Protection, 2025)

Aspergixanthones L−T, nine undescribed prenylxanthone derivatives from Aspergillus stellatus - Yu Liang; Xuanni Chen; Qin Li; Ziming Zhao; Hao Wang; Qingyi Tong; Weiguang Sun; Hucheng Zhu; Yongji Lai; Chunmei Chen; Yonghui Zhang (Phytochemistry, 2025)

Thermal decomposition behavior of retired wind turbine blades: kinetics, pyrolysis product distribution and characterization - Mei Han; Yonghui Bai; Yuan Ma; Peng Lv; Xudong Song; Jiaofei Wang; Weiguang Su; Guangsuo Yu; Xuebin Wang (Journal of Environmental Management, 2025)

X-type and MCM-41-type molecular sieves from full component utilization of coal gasification fine slag and amino modification for CO2 capture - Xueqin Hai; Bin Ma; Qingyun Wang; Xiaqing Liu; Li Ma; Yonghui Bai; Peng Lv; Xudong Song; Guangsuo Yu (Journal of Environmental Management, 2025)

Triterpenoid saponins in tea plants: A spatial and metabolic analysis using UPLC-QTOFMS, molecular networking, and DESI-MSI - Zhenghua Du; Ying Zhou; Shuang Guo; Yonghui Dong; Yongquan Xu; Xiaomin Yu (Food Chemistry, 2025)

Decoupling the factors influencing methanol oxidation performance of Pt3SnCux system based on partial least squares method - Yu Zhang; Hui Li; Xintong Yan; Yonghui Ye; Qianqian Ren; Shi Hu (Chemical Engineering Journal, 2025)

Tandem catalytic upgrading of cow manure pyrolysis vapors by Beta zeolite and nitrogen-doped activated carbon dual catalysts prepared from coal gasification fine slag to produce light aromatic hydrocarbons - Ruofei Wu; Peng Lv; Xuanxuan He; Yonghui Bai; Jiaofei Wang; Juntao Wei; Weiguang Su; Xudong Song; Guangsuo Yu (Journal of Environmental Chemical Engineering, 2025)

Insights on the effects of different macerals in coal on combustion behavior and soot formation: In-situ diagnosis and molecular dynamics simulations - Xuanxuan He; Qifu Luo; Peng Lv; Runmin Wu; Yonghui Bai; Xudong Song; Jiaofei Wang; Weiguang Su; Guangsuo Yu; Weina Bao (Fuel, 2025)

Simulating wind prevention and sand fixation service flow in arid Inland River basins: Insights from the Tarim River basin, China - Wei Yu; Xiaofei Ma; Yonghui Wang; Wei Yan; Chun Luo; Yonglong Han; Binbin Fan (Science of The Total Environment, 2025)

Bipolaristeroid A, a 5,6-seco-9,10-seco-steroid with cytotoxic activity from the fungus Bipolaris maydis - Yong Shen; Lianghu Gu; Qun Zhou; Xiaotian Zhang; Mengru Yu; Qin Li; Yu Liang; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2025)

Coal gasification fine slag as a precursor to prepare mesoporous carbon materials by an activation-hydrothermal two-step method for CO2 adsorption - Xueqin Hai; Bin Ma; Qingyun Wang; Yonghui Bai; Peng Lv; Xudong Song; Xuebin Wang; Guangsuo Yu (Journal of Environmental Management, 2025)

Inhibition effects of wetting and corrosion behavior of high-alkali coal using typical additives under gasification conditions - Jinghong Gao; Weiguang Su; Jiayi Hou; Xudong Song; Yonghui Bai; Jiaofei Wang; Peng Lv; Guangsuo Yu (Fuel, 2025)

Genome-wide elucidation and expression features of Q-type C2H2 zinc finger protein gene family in Rhododendron henanense subsp. lingbaoense - Yonghui Li; Huiping Ma; Siyu Chen; Yao Chen; Xiaojun Zhou; Xiangli Yu; Yafang Zhang; Junwang Han; Hailiang Wang (Genetic Resources and Crop Evolution, 2025)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Higher light utilization and assimilate translocation efficiency produced greater grain yield in super hybrid rice - Xusheng Meng; Yonghui Pan; Yixiao Chai; Yu Ji; Haisu Du; Jian Huang; Shengxian Chen; Min Wang; Shiwei Guo (Plant and Soil, 2024)

Effect of residual carbon on the flow properties of iron-containing coal ash: Ash fusibility and viscosity-temperature characteristics - Wei Zhao; Linmin Zhang; Xudong Song; Yuchen Li; Chaoyue Zhao; Juntao Wei; Yonghui Bai; Peng Lv; Weiguang Su; Guangsuo Yu (Fuel, 2024)

Intrinsic promotion mechanism of calcium oxide on ketone production during catalytic fast pyrolysis of biomass via experiment and density functional theory simulation - Yujie Zhang; Jiaofei Wang; Qifu Luo; Youming Yang; Peng Lv; Weiguang Su; Yonghui Bai; Xudong Song; Guangsuo Yu (Bioresource Technology, 2024)

Y-ring’s mechanical behavior during sealing cap’s assembly process based on the pressure core sampling for seafloor drill - Jialiang Wang; Chen Chen; Yang Sun; Youjia Hu; Mengfei Yu; Deping Peng; Yonghui Tang (Marine Georesources & Geotechnology, 2024)

Three-dimensional solution for braced excavation-induced ground settlement - Hao Li; Maosong Huang; Jian Yu; Yonghui Li; Yuancheng Guo (Computers and Geotechnics, 2024)

The potential benefits and mechanisms of protein nutritional intervention on bone health improvement - Yonghui Yu; Xinping Li; Mengjun Zheng; Linyue Zhou; Jingjie Zhang; Jing Wang; Baoguo Sun (Critical Reviews in Food Science and Nutrition, 2024)

Global sensitivity analysis with deep learning-based surrogate models for unraveling key parameters and processes governing redox zonation in riparian zone - Zhejiong Yu; Heng Dai; Jing Yang; Yonghui Zhu; Songhu Yuan (Journal of Hydrology, 2024)

Insight into N2O emission and denitrifier communities under different aeration intensities in composting of cattle manure from perspective of multi-factor interaction analysis - Yue Han; Ruixin Bi; Yuanhang Wang; Lei Sun; Xinda Liu; Shuai Shi; Nuo Chang; Liyan Zhao; Jiaxin Bao; Yonghui Xu; Wanying Liu; Jining Zhang; et al. (Science of The Total Environment, 2024)

Mitigated N2O emissions from submerged-plant-covered aquatic ecosystems on the Changjiang River Delta - Qingqian Li; Huibin Yu; Peng Yuan; Ruixia Liu; Zhangmu Jing; Yanjie Wei; Shengqiang Tu; Hongjie Gao; Yonghui Song (Science of The Total Environment, 2024)

Statistical physics investigation on the simultaneous adsorption mechanism of Cd2+ and Pb2+ on amino functionalized activated carbon derived from coal gasification fine slag - Bin Liu; Peng Lv; Qingyun Wang; Yonghui Bai; Jiaofei Wang; Weiguang Su; Xudong Song; Guangsuo Yu (Journal of Environmental Chemical Engineering, 2024)

ZnO-In2O3 solid solution hollow tube improved CO2 hydrogenation to methanol via the formate route - Yuchen Shi; Weiguang Su; Xinyu Wei; Xudong Song; Yonghui Bai; Peng Lv; Jiaofei Wang; Guangsuo Yu (Fuel, 2024)

Is cryoablation still suitable for advanced non-small cell lung cancer after failure of first-line chemotherapy? A multicenter, prospective, randomized-controlled trial of eighty-seven patients - Yu Chen; Xueni Fang; Dan Wang; Quanwang Li; Kerui Zhang; Yuan Li; Jinghua Li; Haoyue Pang; Zhiqiang Cheng; Chunyang Zhang; Caiyun Zhang; Wuwei Yang; et al. (Cryobiology, 2024)

Immunosuppressive steroids quadrilisteroids A−C and derivatives from the terrestrial fungus Aspergillus quadrilineatus - Yu Chen; Qin Li; Yu Liang; Mengsha Wei; Hong Liao; Aimin Fu; Weiguang Sun; Chunmei Chen; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2024)

A facile dual-mode immunosensor based on speckle Ag-doped nanohybrids for ultrasensitive detection of Ochratoxin A - Xinke Wang; Xue-xia Jia; Yonghui Wang; Shuang Li; Shuyue Ren; Yu Wang; Dianpeng Han; Kang Qin; Xueyu Chang; Huanying Zhou; Zhixian Gao (Food Chemistry, 2024)

Improving prediction of N2O emissions during composting using model-agnostic meta-learning - Shuai Shi; Jiaxin Bao; Zhiheng Guo; Yue Han; Yonghui Xu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Nana Jiang; Lei Sun; Xinda Liu; Wanying Liu; Nuo Chang; et al. (Science of The Total Environment, 2024)

Penigrines A−E: Five undescribed azepine-indole alkaloids from Penicillium griseofulvum - Yu Liang; Huimin Zhao; Qiwei Wang; Xuanni Chen; Qin Li; Weiguang Sun; Chunmei Chen; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2024)

Applying EEM spectra with absolute principal component coefficients to explore characteristic fingerprints and fractions of DOM from diverse land-use soils in a large-scale irrigation area - Dongping Liu; Miaoxin Bai; Xin Yan; Yonghui Song; Fang Yang; Feng Qian; Huibin Yu (CATENA, 2024)

Evaluating flavonoids as potential aromatase inhibitors for breast cancer treatment: In vitro studies and in silico predictions - Jeong In Seo; Jun Sang Yu; Yonghui Zhang; Hye Hyun Yoo (Chemico-Biological Interactions, 2024)

Microwave synthesis of amino-functionalized MCM-41 from coal gasification fine slag for efficient bidirectional adsorption of anionic and cationic dyes - Zhen Chai; Bin Liu; Peng Lv; Yonghui Bai; Jiaofei Wang; Weiguang Su; Xudong Song; Guangsuo Yu; Guangyu Xu (Chemosphere, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Study on the mechanism of the effect of biomass ash on the erosion and adhesion behavior of Al2O3 ceramic particles - Yuchen Li; Xudong Song; Juntao Wei; Yonghui Bai; Peng Lv; Guangyu Xu; Guangsuo Yu (Fuel, 2024)

Inhibition of O-containing functional groups in coal on the release of alkali metals during co-pyrolysis of coal and biomass in a visual fixed bed combined with laser-induced breakdown spectroscopy - Nanxi Bie; Jiaofei Wang; Peng Lv; Yujie Zhang; Yonghui Bai; Xudong Song; Weiguang Su; Guangsuo Yu (Fuel, 2024)

Trade-offs and synergies among ecosystem services in Inland River Basins under the influence of ecological water transfer project: A case study on the Tarim River basin - Kaixuan Qian; Xiaofei Ma; Wei Yan; Jiaxin Li; Shixian Xu; Yuan Liu; Chun Luo; Wei Yu; Xiaotong Yu; Yahui Wang; Limin Zhou; Yonghui Wang (Science of The Total Environment, 2024)

In situ Raman characterization of the stability of blueberry anthocyanins in aqueous solutions under perturbations in temperature, UV, pH - Chuchu Duan; Xiaofeng Xiao; Yonghui Yu; Mengting Xu; Yanpeng Zhang; Xiaodan Liu; Huang Dai; Fuwei Pi; Jiahua Wang (Food Chemistry, 2024)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Aromatics production from relay catalytic pyrolysis of cow manure using Ru/C and ZSM-5 dual catalysts synthesized from coal gasification fine slag - Ruofei Wu; Peng Lv; Bin Liu; Yonghui Bai; Jiaofei Wang; Juntao Wei; Weiguang Su; Guangyu Xu; Weina Bao; Guangsuo Yu (Journal of Environmental Management, 2023)

High-temperature inter-mineral potassium isotope fractionation in ultrapotassic and granitic rocks: Implications for the potassium isotopic compositions of arc magmas - Tinggen Yang; Haiyang Liu; Yonghui Li; Ying-Yu Xue; Xiaoqiang Li; Kun Wang 王昆; Wei-Dong Sun (Chemical Geology, 2023)

A 219‐year reconstruction of April–June mean minimum temperature from the tree‐ring earlywood density on the Changbai Mountains, China - Ruxianguli· Abudureheman; Tongwen Zhang; Yonghui Wang; Shulong Yu; Ruibo Zhang; Yujiang Yuan; Dong Guo (International Journal of Climatology, 2023)
Using mean earlywood density data from Pinus koraiensis cores, we reconstructed the April–June mean minimum temperature from 1797 to 2015 for the Changbai Mountains. The reconstruction explained 52.6% of the actual mean minimum temperature variance during 1901–2015. After smoothing with an 11‐year moving average, we identified three major cold periods (1797–1875, 1881–1899, and 1903–1946) and three major warm periods (1876–1880, 1900–1902, and 1947–2015) in the reconstructed series. Spatial correlation showed that the reconstruction contained climatic signals for a large area including most of northeast China, especially the Bohai Rim region and the eastern side of the Mongolian Plateau. A comparison between the newly reconstructed temperature series for the surrounding areas reveals similar variations, particularly in the warming trend during the second half of the 20th century. The driving factors of the mean minimum temperature were influenced mainly by the interaction of solar activity and large‐scale atmospheric‐oceanic variability. The reconstructed series provides a basis for understanding past climate change in the Changbai Mountains and for predicting future climate change trends in Northeast China.

Interfacial engineered, hierarchically porous, and underwater superelastic nanofibrous aerogels with rime-mimetic structure for superior micropollutant extraction - Peixin Tang; Binbin Fan; Yonghui Wang; Yang Si; Jianyong Yu; Xueli Wang; Xiyu Song (Chemical Engineering Journal, 2023)

Residual carbon from coal gasification fine slag for inducing rice straw hydrothermal carbonization to achieve improved reactivity and wastewater decontamination - Peng Lv; Bin Liu; Yonghui Bai; Jiaofei Wang; Juntao Wei; Xudong Song; Weiguang Su; Guangsuo Yu; Guangyu Xu (Fuel, 2023)

Night warming from tillering to jointing increases post-anthesis flag leaf photosynthetic capacity and wheat yield - Yonghui Fan; Liangliang Ma; Jinhao Yang; Wenjin Ding; Wei He; Yu Tang; Guoji Cui; Wenjing Zhang; Shangyu Ma; Chuanxi Ma; Zhenglai Huang (European Journal of Agronomy, 2023)

Graded synthesis of high performance adsorbent from coal gasification fine slag and its application in the removal of methyl blue - Bin Liu; Zhen Chai; Peng Lv; Yonghui Bai; Jiaofei Wang; Qinghua Guo; Weiguang Su; Guangsuo Yu (Fuel, 2023)

Insight into the microbial nitrogen cycle in riparian soils in an agricultural region - Chunjian Lyu; Xiaojie Li; Huibin Yu; Yonghui Song; Hongjie Gao; Peng Yuan (Environmental Research, 2023)

Bio-barcode assay: A useful technology for ultrasensitive and logic-controlled specific detection in food safety: A review - Yue Hou; Ruipeng Chen; Zhiguang Wang; Ran Lu; Yonghui Wang; Shuyue Ren; Shuang Li; Yu Wang; Tie Han; Shiping Yang; Huanying Zhou; Zhixian Gao (Analytica Chimica Acta, 2023)

Investigation of underlying links between nitrogen transformation and microorganisms' network modularity in the novel static aerobic composting of dairy manure by “stepwise verification interaction analysis” - Yu Sun; Yonghui Xu; Jining Zhang; Ayodeji Bello; Xiang Li; Wanying Liu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Yue Han; Lijun Cheng; Wenhao Zhang; Qingxin Meng; et al. (Science of The Total Environment, 2023)

Shaking table test of a new special-shaped arch bridge - Kailun Zhang; Airong Liu; Jiyang Fu; Yonghui Huang; Jie Yang; Yuguo Yu; Mao Ye; Zhicheng Yang; Zixiang Zhang (Engineering Structures, 2023)

Insight into suppression of dibutyl phthalate on DOM removal during municipal sewage treatment using fluorescence spectroscopy with PARAFAC and moving-window 2D-COS - Jian Wang; Dongping Liu; Huibin Yu; Yonghui Song (Science of The Total Environment, 2023)

Edible fungi efficiently degrade aflatoxin B1 in cereals and improve their nutritional composition by solid-state fermentation - Haiwei Lou; Chuangming Yang; Ying Gong; Yang Li; Yonghui Li; Shuangqi Tian; Yu Zhao; Renyong Zhao (Journal of Hazardous Materials, 2023)

Preparation of K-N co-doped commercial cylindrical carbon via the coal partial steam gasification for CO2 adsorption - Peng Liu; Jiaofei Wang; Min Yao; Guangsuo Yu; Xudong Song; Peng Lv; Yonghui Bai (Journal of Environmental Chemical Engineering, 2023)

Dynamic investigation on potassium migration and transformation during biochar combustion and its correlation with combustion reactivity - Miao Wang; Deliang Xu; Yonghui Bai; Guangsuo Yu; Junxian Zhang; Shoujun Zhang; Jie Xu; Hong Zhang; Shu Zhang; Juntao Wei (Fuel, 2023)

Separation and characterization of different types of residual carbon in fine slag from entrained flow coal gasification - Qingyun Wang; Yonghui Bai; Peng Lv; Xudong Song; Meng Ma; Yu Shen; Guangsuo Yu; Min Yao (Fuel, 2023)

Catalytic upgrading of cow manure pyrolysis vapors over zeolite/carbon composites prepared from coal gasification fine slag: High quality bio-oil obtaining and mechanism investigation - Ruofei Wu; Peng Lv; Jiaofei Wang; Yonghui Bai; Juntao Wei; Xudong Song; Weiguang Su; Guangsuo Yu (Fuel, 2023)

Latitudinal differentiation and patterns of temperate and subtropical plants in the Qinling-Daba Mountains - Junjie Liu; Baiping Zhang; Yonghui Yao; Xinghang Zhang; Jing Wang; Fuqin Yu; Jiayu Li (Journal of Geographical Sciences, 2023)

Impacts of dibutyl phthalate on bacterial community composition and carbon and nitrogen metabolic pathways in a municipal wastewater treatment system - Jian Wang; Yucheng Tian; Jian Wei; Chunjian Lyu; Huibin Yu; Yonghui Song (Environmental Research, 2023)

Strategy for mapping soil salt contents during the bare soil period through a satellite image: Optimal calibration set combined with random forest - Xibo Xu; Xiaoguang Wang; Peijie Yang; Yonghui Meng; Deqin Yu; Chunfang Li (CATENA, 2023)

Highly active MIL-68(In)-derived In2O3 hollow tubes catalysts to boost CO2 hydrogenation to methanol - Yuchen Shi; Weiguang Su; Xinyu Wei; Xudong Song; Yonghui Bai; Jiaofei Wang; Peng Lv; Guangsuo Yu (Fuel, 2023)

Effect of iron on crystallization and flow properties of coal ash slag: A combined computational-experimental study - Linmin Zhang; Xudong Song; Juntao Wei; Jianrong Yang; Yonghui Bai; Jiaofei Wang; Huijun Yang; Guangsuo Yu (Fuel, 2023)

Recycling of coal gasification fine slag as ultra-high capacity adsorbents for the removal of Rhodamine B dye: Graded synthesis method, kinetics and adsorption mechanism - Zhen Chai; Bin Liu; Peng Lv; Yonghui Bai; Jiaofei Wang; Xudong Song; Weiguang Su; Guangsuo Yu (Fuel, 2023)

In-situ release characteristic of alkali metals during co-pyrolysis of coal and biomass in a visual fixed bed combined with laser-induced breakdown spectroscopy - Nanxi Bie; Jiaofei Wang; Peng Lv; Yujie Zhang; Yonghui Bai; Xudong Song; Weiguang Su; Guangsuo Yu (Fuel, 2023)

Depth and Heading Control of a Manta Robot Based on S-Plane Control - Yue He; Yu Xie; Guang Pan; Yonghui Cao; Qiaogao Huang; Shumin Ma; Daili Zhang; Yong Cao (Journal of Marine Science and Engineering, 2022)
Bionic underwater robots have many advantages such as high mobility, high efficiency, high affinity, etc. They are especially suitable for tasks such as collecting hydrographic information and for detailed surveys of the marine environment. These tasks are based on their high-precision attitude control. Therefore, this paper proposes a control scheme for a bionic underwater robot—a manta robot. To improve the depth retention capability of the manta robot, a S-plane controller based on asymmetric output was designed in combination with the longitudinal motion characteristics of the manta robot. In addition, to achieve good motion control for the manta robot under conditions of large changes in the heading angle, the fuzzy controller and the heading transition target value function were combined to design the heading controller of the manta robot. Finally, the feasibility and reliability of the control system of the manta robot were verified by pool experiments. The experimental results showed that the depth control error was within ±5 cm and the heading control error was within ±5 degrees. The control scheme proposed in this paper achieves high-precision attitude control of the manta robot, providing a basis for the practical application of the manta robot.

The classical and potential novel healthy functions of rice bran protein and its hydrolysates - Yonghui Yu; Goutom Kumar Gaine; Linyue Zhou; Jingjie Zhang; Jing Wang; Baoguo Sun (Critical Reviews in Food Science and Nutrition, 2022)

Bioinspired Central Pattern Generator and T-S Fuzzy Neural Network-Based Control of a Robotic Manta for Depth and Heading Tracking - Yonghui Cao; Yu Xie; Yue He; Guang Pan; Qiaogao Huang; Yong Cao (Journal of Marine Science and Engineering, 2022)
Aiming at the difficult problem of motion control of robotic manta with pectoral fin flexible deformation, this paper proposes a control scheme that combines the bioinspired Central Pattern Generator (CPG) and T-S Fuzzy neural network (NN)-based control. An improved CPG drive network is presented for the multi-stage fin structure of the robotic manta. Considering the unknown dynamics and the external environmental disturbances, a sensor-based classic T-S Fuzzy NN controller is designed for heading and depth control. Finally, a pool test demonstrates the effectiveness and robustness of the proposed controller: the robotic manta can track the depth and heading with an error of ±6 cm and ±6°, satisfying accuracy requirements.

Dehydroabietic acid improves nonalcoholic fatty liver disease through activating the Keap1/Nrf2-ARE signaling pathway to reduce ferroptosis - Gai Gao; Zhishen Xie; Er-wen Li; Yong Yuan; Yu Fu; Pan Wang; Xiaowei Zhang; Yonghui Qiao; Jiangyan Xu; Christian Hölscher; Hui Wang; Zhenqiang Zhang (Journal of Natural Medicines, 2021)

North-south vegetation transition in the eastern Qinling-Daba Mountains - Xinghang Zhang; Baiping Zhang; Jing Wang; Fuqin Yu; Chao Zhao; Yonghui Yao (Journal of Geographical Sciences, 2021)

Characterizing humic substances from a large-scale lake with irrigation return flows using 3DEEM-PARAFAC with CART and 2D-COS - Xiu Han; Huibin Yu; Yonghui Song; Yingying Chen; Chongwei Li; Qi Qi (Journal of Soils and Sediments, 2020)

Assessment of high-resolution satellite rainfall products over a gradually elevating mountainous terrain based on a high-density rain gauge network - Linfei Yu; Lexin Ma; Huilong Li; Yongqiang Zhang; Fanchao Kong; Yonghui Yang (International Journal of Remote Sensing, 2020)

Revealing the Mechanism of EGCG, Genistein, Rutin, Quercetin, and Silibinin Against hIAPP Aggregation via Computational Simulations - Yu Wang; Yonghui Lv; Liang Jin; Guizhao Liang (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Novel contrast media based on the liquid metal gallium for in vivo digestive tract radiography: a feasibility study - Huan Liu; Yang Yu; Wei Wang; Ying Liu; Yonghui An; Qian Wang; Jing Liu (BioMetals, 2019)

Acute downregulation of miR-155 leads to a reduced collagen synthesis through attenuating macrophages inflammatory factor secretion by targeting SHIP1 - Longlong Yang; Lingying Liu; Huinan Ying; Yonghui Yu; Donghai Zhang; Huping Deng; Haijun Zhang; Jiake Chai (Journal of Molecular Histology, 2018)

Characterization of dissolved organic matter in Dongjianghu Lake by UV-visible absorption spectroscopy with multivariate analysis - Yanzhong Zhu; Yonghui Song; Huibin Yu; Ruixia Liu; Lusan Liu; Chunjian Lv (Environmental Monitoring and Assessment, 2017)

Tracking fluorescent components of dissolved organic matter from soils in large-scale irrigated area - Hongwei Pan; Huibin Yu; Yonghui Song; Lin Zhu; Ruixia Liu; Erdeng Du (Environmental Science and Pollution Research, 2017)

Synchronous fluorescence spectroscopy combined with two-dimensional correlation and principle component analysis to characterize dissolved organic matter in an urban river - Huibin Yu; Yonghui Song; Hongwei Pan; Jianfeng Peng; Hongjie Gao; Ruixia Liu (Environmental Monitoring and Assessment, 2016)

A statistical model for karst spring discharge estimation under extensive groundwater development and extreme climate change - Yu Zhong; Yonghong Hao; Xueli Huo; Mingkun Zhang; Qingyun Duan; Yonghui Fan; Yan Liu; Youcun Liu; Tianchyi J. Yeh (Hydrological Sciences Journal, 2016)

Comparison of PARAFAC components of fluorescent dissolved and particular organic matter from two urbanized rivers - Huibin Yu; Yonghui Song; Erdeng Du; Nan Yang; Jianfeng Peng; Ruixia Liu (Environmental Science and Pollution Research, 2016)

Pubertal exposure to di-(2-ethylhexyl)-phthalate inhibits G9a-mediated histone methylation during spermatogenesis in mice - Chuan Liu; Peng Qian; Lingling Yang; Lei Zhang; Chunhai Chen; Mindi He; Yonghui Lu; Wei Feng; Min Li; Yanwen Zhang; Min Zhong; Zhengping Yu; et al. (Archives of Toxicology, 2016)

Transgenic analysis reveals LeACS-1 as a positive regulator of ethylene-induced shikonin biosynthesis in Lithospermum erythrorhizon hairy roots - Rongjun Fang; Fengyao Wu; Ailan Zou; Yu Zhu; Hua Zhao; Hu Zhao; Yonghui Liao; Ren-Jie Tang; Tongyi Yang; Yanjun Pang; Xiaoming Wang; Rongwu Yang; et al. (Plant Molecular Biology, 2016)

Anti-inflammatory phenolic glycosides from Liparis odorata - Yonghui Xie; Songhua Yu; Hongdong Liu; Dongming Zhang; Xuewen Lai; Bo Liu; Bin Li (Medicinal Chemistry Research, 2015)

DISC1 Ser704Cys impacts thalamic-prefrontal connectivity - Bing Liu; Lingzhong Fan; Yue Cui; Xiaolong Zhang; Bing Hou; Yonghui Li; Wen Qin; Dawei Wang; Chunshui Yu; Tianzi Jiang (Brain Structure and Function, 2015)

Variation of dissolved fulvic acid from wetland measured by UV spectrum deconvolution and fluorescence excitation-emission matrix spectrum with self-organizing map - Huibin Yu; Yonghui Song; Ruixia Liu; Beidou Xi; Erdeng Du; Shuhu Xiao (Journal of Soils and Sediments, 2014)

A study of the contribution of mass elevation effect to the altitudinal distribution of timberline in the Northern Hemisphere - Fang Zhao; Baiping Zhang; Yu Pang; Yonghui Yao (Journal of Geographical Sciences, 2014)

Bisphenol A exposure at an environmentally relevant dose induces meiotic abnormalities in adult male rats - Chuan Liu; Weixia Duan; Lei Zhang; Shangcheng Xu; Renyan Li; Chunhai Chen; Mindi He; Yonghui Lu; Hongjuan Wu; Zhengping Yu; Zhou Zhou (Cell and Tissue Research, 2014)

MicroRNA-142-3p inhibits cell proliferation in human acute lymphoblastic leukemia by targeting the MLL-AF4 oncogene - Liping Dou; Jingxin Li; Dehua Zheng; Yonghui Li; Xiaoning Gao; Chengwang Xu; Li Gao; Lili Wang; Li Yu (Molecular Biology Reports, 2013)

Application of chemometrics to spectroscopic data for indicating humification degree and assessing salinization processes of soils - Huibin Yu; Yonghui Song; Beidou Xi; Xinghui Xia; Xiaosong He; Xiang Tu (Journal of Soils and Sediments, 2012)

Diversity and geographical pattern of altitudinal belts in the Hengduan Mountains in China - Yonghui Yao; Baiping Zhang; Fang Han; Yu Pang (Journal of Mountain Science, 2010)